THE EVOLUTION OF CINEMATOGRAPHY IN RUSSIAN LITERATURE OF THE 1920S - Nikolaeva, Valentina A.; Fesyanova, Natalia L.; Goryacheva, Olga N. (Gênero & Direito, 2019)
This paper concerns the issue of the interaction of literature and cinematography in the cultural process of the 1920s. The main emphasis is placedon the phenomenon of literary cinematography, which became widespread in the third decade of the 20th century. The content of the concept of “cinematographic literature”is defined, its significant characteristics are singled out (special compositional-syntactic organization of the work, representation of the situation of observation, the use of cinema techniques) and the development of cinematography in the work of poets and writers of the period is studied. Inthecourseof the analysis of thetexts, specific techniques and cinematographic functions characteristic of this decade were singledout. Experimenting with artistic time and space, the authors attach an innovative character to the works, develop new ways of constructing the plot. In addition, cinematography makes it possible to add the text documentary and agitationality. The study revealed a close relationship between the development of cinematography in the literature and the general tendencies of the cultural process of the early 20th century.